Psittacosis, an Uninvited Guest - Soma Dutta; Ujjwayini Ray (Journal of Global Infectious Diseases, 2025)
Psittacosis is a zoonotic disease caused by the bacteria Chlamydia psittaci. It commonly presents with flu-like symptoms and community-acquired pneumonia (CAP). The bacteria is transmitted from birds to humans. The most common bird is parrots. Here, we present a cluster of cases of psittacosis in a family which led to the hospitalization of all the five members of the family. All the five patients presented with fever, weakness, dry cough, and dyspnea on exertion. Chlamydia psittaci immunoglobulin M was detected by indirect immunofluorescence assay. The family had a history of contact with parrots. The patients were treated with doxycycline and recovered without any complications. Psittacosis is an uncommon cause of CAP which can have a wide range of presentations, from being asymptomatic, to flu-like symptoms or to fulminant disease. Elaborate history and a high degree of suspicion are very important to come to the diagnosis. The infection is easily treatable with appropriate antibiotics. Public awareness and education regarding the zoonotic transmission of disease can reduce disease incidence.